Kualitas Pelayanan Administrasi Pada Jurusan Administrasi Publik Fakultas Ilmu Sosial Universitas Negeri Gorontalo - Fendi Pernata; Rusli Isa; Sri Yulianty Mozim (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aimed to identify and describe the quality of administrative services in the Department of Public Administration, Faculty of Social Sciences, Universitas Negeri Gorontalo. The research employed a qualitative descriptive approach, collecting data through observation, in-depth interviews, and documentation. The research focused on five key aspects of administrative service quality: Tangible, Empathy, Reliability, Responsiveness, and Assurance. The findings indicated that the quality of administrative services in the department still faced several challenges, including limited facilities and infrastructure, unwelcoming and less attentive staff attitudes, poor implementation of Standard Operating Procedures (SOPs), and insufficient responsiveness and service assurance from administrative personnel. Both internal and external factors, such as facility limitations and high customer expectations, also affected the quality of services provided. This research was expected to serve as a reference for evaluation and improvement to enhance the quality of administrative services in higher education institutions, particularly within the Department of Public Administration, Faculty of Social Sciences, Universitas Negeri Gorontalo.